Fluorine-free preparation of a superhydrophobic coating with anti-icing properties, mechanical durability and self-cleaning effect. Issue 4 (10th January 2023) - Yu, Meiling; Li, Xu; Tan, Xinyu; Chen, Xiaobo
Abstract : Superhydrophobic materials have become a feasible choice to solve related difficult problems because of their excellent anti-icing, anti-corrosion, and self-cleaning characteristics. Abstract : Superhydrophobic materials have become a feasible choice to solve related difficult problems because of their excellent anti-icing, anti-corrosion, and self-cleaning characteristics. In this work, a superhydrophobic hydroxypropyl methylcellulose (HPMC)/SiO2 coating is prepared using an efficient, fluorine-free method for the anti-icing application of transmission line insulators and other similar material surfaces. The water contact angle (WCA) of the coating is 161°, and the slide angle (SA) is less than 1°. The coating maintains good hydrophobicity after mechanical durability tests. In the anti-icing performance tests, the start freezing time of a single droplet is delayed by 1366 s, and when the surface is not coated, the ice amount is more than twice that with the coating. Therefore, this work provides a straightforward and promising solution to solving high-cost and low-efficiency difficulties in the anti-icing problem of transmission line insulators and other similar material surfaces.